1983
DOI: 10.1161/01.hyp.5.2.240
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic normotensive primary aldosteronism. Case report.

Abstract: SUMMARY We report a case of primary aldosteronism in a 30-year-old woman without hypertension or any other characteristic symptoms. The condition was first suspected by hypokalemia (2.6 mEq/liter), which was incidentally found by routine checkup. There was evidence of suppressed plasma renin activity (PRA) and elevated plasma aldosterone levels. However, the blood pressure never reached a hypertensive level, and the circulating blood volume was within a normal range. A functioning right adrenal tumor was diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…Only 16 cases of normotensive primary hyperaldosteronism have been reported in the literature, with only 10 in the English literature (5)(6)(7)(8)(9)(10)(11)(12)(13)(14). About 75% of cases were described in Eurasians (especially Japanese).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Only 16 cases of normotensive primary hyperaldosteronism have been reported in the literature, with only 10 in the English literature (5)(6)(7)(8)(9)(10)(11)(12)(13)(14). About 75% of cases were described in Eurasians (especially Japanese).…”
Section: Discussionmentioning
confidence: 99%
“…Arterial hypertension could be related to the early diagnosis of hyperaldosteronism (5,7,8,10,11). However, the 3-year history of hypokalemia in the first patient, and the second patient's blood pressure stability for more than one year before surgery despite hypokalemia, argue against this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There have been several case reports, describing PA without hypertension, [25][26][27][28][29][30][31] although the reason for the absence of hypertension has not been clarified in any of the cases of normotensive PA reported. It is suggested that a short duration of hyperaldosteronemia could explain normotension in those patients.…”
mentioning
confidence: 99%